Feasibility and initial outcomes of a multifaceted prevention programme of melioidosis in diabetic patients in Ubon Ratchathani, northeast Thailand. - Pornpan Suntornsut; Wipada Chaowagul; Wilasinee Thongklang; Thidarat Phosri; Nicholas P J Day; Susan Michie; Direk Limmathurotsakul (Public Library of Science (PLoS), 2018)
BACKGROUND:Melioidosis is an infection caused by Burkholderia pseudomallei, a Gram-negative bacillus found in soil and water. Diabetes mellitus is the most important risk factor for melioidosis. The recommendations for disease prevention include avoiding direct contact with soil and water, and drinking only boiled or bottled water. METHODS:A prospective intervention study was conducted to evaluate the feasibility and behavioural outcomes of a multifaceted prevention programme for melioidosis. Participants were diabetic adults in Ubon Ratchathani, northeast Thailand. Ten behavioural support groups consisting of 6 to 10 participants per group were conducted. Twelve behaviour change techniques were used: information about health consequences, credible source, adding objects to the environment, reconstructing the physical environment, instruction on how to perform a behaviour, demonstration of the behaviour, commitment, prompts/cues, self-monitoring of behaviour, goal setting, feedback on behaviour, and social support, and their feasibilities evaluated. RESULTS:There were 70 participants, of median age 59 years and 52 (74%) were female. Participants found the intervention beneficial, interesting and engaging. Participants indicated that they liked to watch videos with information about melioidosis delivered by local doctors and patients who survived melioidosis, and videos showing use of over-the-knee boots by local farmers. Participants felt engaged in the sessions that trialed protective gear and that made calendars with individual photographs and self-pledges as a reminder tool. The proportions of participants reporting that they always wore boots while working in rice fields increased from 30% (10/33) to 77% (28/37, p = 0.04), and that they drank only boiled or bottle water increased from 43% (30/70) to 86% (59/69, p<0.001) at 6 months post intervention. CONCLUSION:The programme is highly acceptable to participants, and can support behaviour change. Policy makers should consider implementing the programme in areas where melioidosis is endemic. Making calendars with individual photographs and self-pledges as a reminder tool could be powerful in behaviour change interventions, and further research on this component is needed.